The university incubators of a solidarity economy in Brazil. A case study - Fátima Cruz-Souza (AECOOP Escuela de Estudios Cooperativos, 2011)
The Solidarity Economy is a social movement who is growing up in the last 15 years in Brazil and it includes a very big group of socioeconomic actors. This movement improves alternatives of productive insertion to disadvantage groups of population. However its objectives are not only the economic changes, but the promotion of social and cultural changes toward a more equal and solidarity society. To support and strengthen the solidarity economy, the Popular Cooperatives Incubators had been created in some Brazilian Universities. In this study we analyse the path of the Regional Incubators of Popular Cooperatives of Federal University of San Carlos (State of São Paulo, Brazil). It works as a structure which combines research, learning and university extension to improve incubation process of solidarity entrepreneurship. Through the case study we try to know the conceptual and methodologial progress that is related with the difficulties founded by the consolidation of solidarity entrepreneurs and to creation of networks between solidarity economics initiatives in their territories. The study of this process helps us to identify and discuss about strategies to improve the conceptual framework and the advice methodology, and to transfer the results to other initiatives.